On the non-classical crystallographic slip in Tin+1AlCn MAX phases. (15th March 2021) - Zhan, Zhiqiang; Radovic, Miladin; Srivastava, Ankit
Abstract: In this work, we investigate the effect of atomic stacking on non-classical (non-Schmid) crystallographic slip in a class of atomically layered ternary carbides referred to as MAX phases with general formula Mn+1 AXn, where the value of n represents the stacking sequence. To this end, we have carried out compression tests on single crystal micropillars of Ti3 AlC2 with a range of crystallographic orientations and compared the results with that of Ti2 AlC. Our results show that similar to Ti2 AlC, Ti3 AlC2 also exhibits non-classical crystallographic slip, wherein the crystallographic slip depends on both the resolved shear stress and the stress normal to the slip plane. However, for crystallographic slip, the intrinsic critical resolved shear stress in Ti3 AlC2 is greater than Ti2 AlC, while the frictional resistance in Ti3 AlC2 is smaller than Ti2 AlC. The implications of these findings on the macroscopic response of polycrystalline aggregates of these two MAX phases is also discussed. Graphical abstract: Image, graphical abstract